Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning (PBL) Pada Materi Sistem Indera Untuk Melatih Keterampilan Berpikir Kritis Siswa - Annisa Purba; Khairuna Khairuna; Miza Nina Adlini (Badan Penerbit STIEPARI Press, 2023)
This research aims to determine the development of student worksheets (LKPD) based on problem based learning (PBL) on sensory system material to train students' critical thinking skills. This research is development research (RnD) which uses the 4D (four-D) development model. The research population was high school students in class XI Science with a sample size of 30 respondents. Data collection techniques were carried out using questionnaires, interviews, observation and documentation. The data analysis technique uses two techniques, namely qualitative and quantitative. The research results showed that the validity test was obtained from 3 validators, namely material expert validator, media expert validator and pretest posttest expert validator. The average percentage of material experts is 88.88% in the very valid category, the average percentage of media experts is 75% in the valid category, the average percentage of pretest posttest experts is 100% in the very valid category. The practicality test obtained from educators with an average percentage of 88.33% and students with an average of 100% is included in the very practical category. The effectiveness test was obtained through pretest results with an average of 46.17% and posttest results with an average of 74.67% including the effective category. From the research results, it can be concluded that learning using Problem Based Learning (PBL) based LKPD can train students' critical thinking skills.